Brown Bear (Ursus arctos) Predation of Broad Whitefish (Coregonus nasus) in the Mackenzie Delta Region, Northwest Territories - Barker, Oliver E.; Derocher, Andrew E. (ARCTIC, 2009)
On 2 October 2007, we observed evidence of at least one brown bear (Ursus arctos) predating and caching broad whitefish (Coregonus nasus) at Pete’s Creek, a tributary of the Mackenzie River, Northwest Territories. While predation on whitefish by brown bears has been reported as traditional ecological knowledge in the Northwest Territories, accounts in the scientific literature of brown bears feeding on fish other than salmon, trout (Oncorhynchus spp.), and charr (Salvelinus spp.) are rare, particularly for North America. As a spatially concentrated, high-quality food in a resource-poor landscape, migrating broad whitefish may play an important role in the foraging ecology of some Arctic brown bears. Le 2 octobre 2007, nous avons observé au moins un ours brun (Ursus arctos) en train de s’attaquer à un corégone tschir (Coregonus nasus) et de le cacher à Pete’s Creek, un affluent du fleuve Mackenzie, dans les Territoires du Nord-Ouest. Bien que les connaissances écologiques traditionnelles des Territoires du Nord-Ouest attestent de la prédation de corégones par les ours bruns, il est rare que la documentation scientifique démontre que les ours bruns mangent du poisson autre que le saumon, la truite (Oncorhynchus spp.) et l’omble chevalier (Salvelinus spp.), particulièrement en Amérique du Nord. En tant que source alimentaire de grande qualité concentrée dans cet espace et ce paysage pauvre en ressources, le corégone tschir en migration pourrait jouer un rôle important dans l’écologie alimentaire de certains ours bruns de l’Arctique.